Coronavirus disease 2019 associated with aggressive neurological and mental abnormalities confirmed based on cerebrospinal fluid antibodies: A case report. Issue 36 (4th September 2020) - Wang, Maomao; Li, Ting; Qiao, Fan; Wang, Laixing; Li, Chunlin; Gong, Yanping
Abstract: Introduction: Coronavirus disease (COVID-19) is spreading worldwide. The reported possible neurological symptoms are varied and range from subtle neurologic deficits to unconsciousness. Knowledge regarding the detection, diagnosis, treatment, and follow-up of COVID-19-associated neurological damage is still limited. We report a case of serious neurological damage and mental abnormalities in a patient who was finally confirmed to have COVID-19 based on IgM and IgG antibodies in the cerebrospinal fluid (CSF). Patient concerns: A 68-year-old man had slight flu-like symptoms and transient loss of consciousness in early February. Exaggerated unconsciousness and deteriorating mental abnormalities occurred over the next month without severe respiratory symptoms. Craniocerebral computed tomography showed normal results, but antibodies against severe acute respiratory syndrome coronavirus 2 were 100 times higher in the CSF than in the serum; tests for viral ribonucleic acid showed negative results with both a nasopharyngeal swab and CSF sample. Diagnosis: COVID-19 pneumonia was diagnosed based on symptoms and positive results for IgM and IgG in the CSF. Interventions: Antiviral, fluid, and nutritional support were administered for 30 days before admission without obvious improvement. A further 18 days of routine antiviral therapy, immunoglobulin therapy (10 g per day for 5 days), and antipsychotic drug treatment were administered. Outcomes: The patient's neurological and mental abnormalities were greatly ameliorated. He was discharged with mild irritability, slight shaking of the hands, and walking fatigue. These symptoms have persisted up to our last follow-up (May 4, 2020). Conclusion: We believe this is the first case involving neural system injury in a patient who confirmed COVID-19 based on CSF antibody test results. Negative ribonucleic acid test results, strong positivity for antibodies, and high protein levels in the CSF suggest the possibility of autoimmune encephalitis secondary to COVID-19. This case highlights additional novel symptoms of COVID-19, and these data are important for the assessment and follow-up of COVID-19 patients.